Hubungan Efikasi Diri dengan Stres Kerja pada Petani Tembakau di Kecamatan Kalisat-Jember - Andriyani, Alfia; Wuryaningsih, Emi; K, Enggal Hadi (Pustaka Kesehatan, 2023)
The increase in self-efficacy in tobacco farmers has an important role related to occupational stress management. This research aimed to analyze the correlation between self-efficacy with the occupational stress of tobacco farmers in the subdistrict Kalisat Regency Jember. The method of this research was a cross-sectional study with 100 tobacco farmers using a cluster sampling technique. The study was conducted in April in Kalisat District, Jember Regency. Bivariate analysis used Pearson correlation (α <0.1; CI = 90%). The research instrument of self-efficacy used GSE (General Self-Efficacy) with α Cronbach =0.76-0.9 and DASS (Depression Anxiety Stress Scale) with α cronbach=0.88. This research has passed the research feasibility through the Health Research Ethics Commission (KEPK) of the Faculty of Dentistry, University of Jember No. 270/UN 25.8./KEPL/DL. The results showed high self-efficacy (30,31%) and low occupational stress (17,39%). The results of the univariate analysis showed high self-efficacy with an average value of 30,31% (sd= 5,75) and low occupational stress with an average value of 17,39 (sd=5,79). The results of the bivariate analysis showed that there was a significant relationship between self-efficacy and occupational stress with Pearson correlation values ​​p <0,000 (α <0.1; CI = 90%). Behavior showed by the tobacco farmers is that they highly believe themselves to work in tobacco farms. One who has high self-efficacy is able to overcome occupational stress. The results of this study are expected to help to improve occupational health services. This functioned to maintain and improve the health status of tobacco farmers.